Sidewalk antiskid terrace material and construction process thereof
By compounding a variety of high-performance resins with nanofillers and combining them with modified flame retardants, a dense coating is formed, which solves the problems of insufficient hardness, anti-slip performance and weather resistance of existing epoxy floor coatings, and achieves improvements in the mechanical strength, anti-slip effect and flame retardant properties of high-performance floor materials.
Patent Information
- Application Number
- CN202510985062.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-17
- Publication Date
- 2025-10-10
AI Technical Summary
Existing epoxy floor coatings have deficiencies in hardness, anti-slip performance, weather resistance and chemical resistance, which limits their application in the field of high-performance flooring.
A variety of high-performance resins and nano-fillers are used to form a dense and uniform coating. Combined with modified flame retardants, the mechanical strength, anti-slip effect and flame retardant properties are improved. Through scientific formula and construction technology, the coating has strong adhesion and is easy to construct.
It significantly improves the mechanical strength, anti-slip performance, wear resistance and flame retardancy of the floor, making it suitable for long-term use on outdoor sidewalks. It combines beauty and practicality and meets public safety requirements.
Smart Images

Figure CN120758119A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of floor material manufacturing, and in particular to an anti-slip floor material for a sidewalk and a construction process thereof. Background Art
[0002] Epoxy floor coatings, due to their excellent mechanical properties, chemical stability, and decorative effects, are widely used in floor construction applications in industrial plants, warehouses and logistics, electronics manufacturing, food processing, and public spaces. With increasing demand for functional and safe flooring, traditional epoxy flooring must not only possess basic properties such as wear resistance, pressure resistance, and impact resistance, but also meet multiple requirements such as corrosion resistance, anti-slip properties, and decorative properties. This is especially true in public areas such as sidewalks, where flooring materials must balance anti-slip safety with environmental resistance to prevent slips and falls. Furthermore, they must also possess higher requirements for wear resistance and UV resistance.
[0003] Although some flame retardant epoxy floor coatings on the current market can meet higher fire protection standards, taking the Chinese patent with authorization number CN103571304B as an example, it discloses a flame retardant epoxy floor coating. The invention specifically discloses that the flame retardant epoxy floor coating is composed of a main agent and a curing agent mixed in a weight ratio of 100: (20-30), and the main agent is composed of the following raw materials in parts by weight: 40-70 parts of epoxy resin, 2-10 parts of diluent, 30-50 parts of flame retardant, 0.01-2 parts of dispersant, 0.01-2 parts of defoaming agent, and 0.01-2 parts of leveling agent. .01-2 parts, colorant 1-5 parts; the curing agent is composed of the following raw materials in the following weight proportions: polyether amine 30-90 parts, active amine 10-70 parts, accelerator 1-10 parts; this flame retardant epoxy floor coating is different from the products on the market and can achieve UL94V0 fire resistance grade, but it still has defects such as insufficient hardness, poor anti-slip performance, insufficient weather resistance and chemical resistance, which limits its application in the field of high-performance flooring.
[0004] On the other hand, with the increasing demand for diversified floor materials in industry and public facilities, such as high temperature resistance, flame retardancy, anti-slip and environmentally friendly low-volatile properties, the development of high-performance floor coatings with multifunctionality has become a development trend.
[0005] Purpose of the Invention In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a non-slip floor material for sidewalks and a construction process thereof, which belongs to the field of floor material manufacturing technology. The non-slip floor material for sidewalks is compounded with a variety of high-performance resins and nano-fillers to form a dense and uniform coating, which significantly improves the mechanical strength and wear resistance of the floor. In addition, the application of modified flame retardants gives the floor a good flame retardant effect and improves safety. The overall formula and construction process are scientific and reasonable, ensuring that the coating has strong adhesion, simple construction and sufficient curing, suitable for long-term use on outdoor sidewalks, and has both aesthetics and practicality.
[0006] To achieve the above object, the present invention provides the following technical solutions: A non-slip floor material for sidewalks comprises the following components, in parts by mass: 30-40 parts of epoxy resin, 15-20 parts of polysiloxane elastic resin, 10-15 parts of fluorocarbon resin, 4-5 parts of modified covalent organic framework nanosheets, 3-5 parts of boron nitride nanotubes, 10-12 parts of nano silicon nitride particles, 3-4 parts of nano silicon dioxide, 2-3 parts of nano zinc oxide, 7-8 parts of modified flame retardant, 6-7 parts of attapulgite, 4-6 parts of curing agent, 1.5-2 parts of accelerator, 0.5-1 part of leveling agent, 1-2 parts of coupling agent, and 1.5-2 parts of dispersant.
[0007] Preferably, the modified covalent organic framework nanosheets are prepared by the following steps: S11. Weigh 1-3 parts of 2,4,6-trihydroxybenzaldehyde and 1-3 parts of p-phenylenediamine by mass, add them to 20-30 parts of dimethyl sulfoxide and mix them, and stir them with ultrasonic assistance for 10-15min to ensure complete mixing; S12. The mixed solution was heated in an oil bath to 120-130°C and reacted for 24-32 hours to perform a heating condensation reaction. After the reaction, the mixture was cooled to room temperature, centrifuged, washed, and dried to obtain covalent organic framework nanosheets. S13. Dispersing the covalent organic framework nanosheets in a sodium hydroxide aqueous solution with a pH of 9-10, reacting at 30-40° C. for 2-3 hours, promoting the ring-opening and cleavage of the imine bonds at the edge of the framework to generate -NH2 and -OH hydroxyl groups, thereby increasing the hydroxyl content and obtaining the modified covalent organic framework nanosheets.
[0008] Preferably, the modified flame retardant is prepared by the following steps: S21. 3-4 parts by mass of magnesium hydroxide nanopowder was added to 80-100 parts of a 1-3 mol / L aqueous HCl solution, ultrasonically dispersed for 10-20min, and the pH of the solution was adjusted to 2-3; S22. 0.6-1.2 parts by mass of aniline was added to 20-30 parts of a 1-3 mol / L aqueous HCl solution, and ultrasonicated until the aniline was completely dissolved to form a homogeneous solution; S23. 1.2-1.5 parts by mass of ammonium persulfate was added to 20-30 parts of a 1-3 mol / L aqueous HCl solution, and sonicated until the ammonium persulfate was completely dissolved to form a homogeneous solution; S24. The aniline solution was added to the magnesium hydroxide suspension and stirred evenly. The temperature was controlled at 0-5 ° C in an ice bath. The ammonium persulfate solution was added dropwise to carry out the polymerization reaction. Stirring was continued during the addition and the temperature was maintained at no more than 5 ° C. After the addition was completed, stirring was continued for 4-5h to ensure that the polyaniline was evenly coated with the magnesium hydroxide particles; S25. After the reaction is completed, the precipitate is collected by centrifugation, washed, and dried to obtain the modified flame retardant.
[0009] Preferably, the anti-slip floor material for sidewalks is prepared by the following steps: S31. The epoxy resin, the polysiloxane elastic resin and the fluorocarbon resin were mixed in parts by mass, and a coupling agent was added to enhance the interfacial bonding to obtain a resin matrix; S32. The nano-silicon nitride particles, nano-silicon dioxide, nano-zinc oxide, boron nitride nanotubes, modified covalent organic framework nanosheets, attapulgite and dispersant were added to the resin matrix prepared in step S31 in parts by mass, and stirred for 2-3h to mix evenly; S33. Add modified flame retardant, curing agent, accelerator and leveling agent in order by mass, and continue stirring for 1-2 hours to obtain the anti-slip floor material for the sidewalk.
[0010] Preferably, the diameter of the boron nitride nanotubes is in the range of 20-50 nm; the particle size of the nano silicon nitride is in the range of 50-100 nm; the particle size of the nano silicon dioxide is in the range of 20-50 nm; and the particle size of the nano zinc oxide is in the range of 10-100 nm.
[0011] Preferably, the curing agent is further limited to a dicyandiamide curing agent.
[0012] Preferably, the leveling agent is further defined as a polysiloxane leveling agent.
[0013] Preferably, the coupling agent is further limited to a silane coupling agent.
[0014] Preferably, the accelerator is further defined as a 2-methylimidazole accelerator.
[0015] A construction process for a sidewalk anti-skid floor material, used for laying the sidewalk anti-skid floor material, is characterized by comprising the following steps: S1. Clean, sand and remove dust from the sidewalk base and apply primer; S2. After the primer is dry, apply the epoxy mid-coat. After the epoxy mid-coat is dry, use a roller to evenly apply the mixed sidewalk anti-slip floor material on the surface of the epoxy mid-coat. After natural curing for 10-15 days, the paving is completed.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The anti-slip floor material for sidewalks prepared by the present invention achieves excellent comprehensive performance through the scientific proportioning and reasonable design of multiple high-performance components. Epoxy resin, as the main matrix material, provides good mechanical strength, adhesion and chemical stability. Its epoxy groups are cross-linked under the action of a curing agent to form a three-dimensional network structure, which enables the coating to have excellent wear resistance, pressure resistance and impact resistance, thereby ensuring the long-term service life of the floor. The polysiloxane elastic resin gives the coating good flexibility and elasticity, which can effectively buffer external force impacts, reduce the risk of cracks and peeling, and at the same time improve the heat resistance and stability of the coating to adapt to changing ambient temperatures. In addition, the addition of fluorocarbon resin significantly enhances the weather resistance and UV resistance of the coating, prevents fading and powdering caused by long-term exposure to outdoor environments, and improves the corrosion resistance of the coating; 2. Modified covalent organic framework nanosheets are prepared via organic synthesis. Alkaline modification increases the surface hydroxyl content, promoting interfacial bonding with the resin matrix, enhancing the nanosheet dispersion and the coating's mechanical strength and wear resistance. Boron nitride nanotubes, with their excellent thermal stability and mechanical properties, provide a reinforcing framework for the coating, improving crack resistance and heat resistance. Furthermore, they form hydrogen bonds through BN bonds with the imine bonds (-C=N-) in the covalent organic framework nanosheets, creating a "sheet-tube" support structure. Inorganic nanoparticles such as nano-silicon nitride, nano-silicon dioxide, and nano-zinc oxide act as fillers, increasing the coating's density and hardness, enhancing its wear and scratch resistance. Nano-zinc oxide also offers UV and antibacterial properties, further improving the coating's durability. A modified flame retardant, a composite of nano-magnesium hydroxide and polyaniline, releases water during combustion, lowering the temperature and forming a MgO ceramic layer and a protective carbon layer that effectively block oxygen and heat conduction, significantly enhancing the coating's flame retardancy and meeting public safety requirements for pedestrians. Attapulgite acts as a nanofiller dispersant, promoting uniform distribution of nanoparticles and preventing agglomeration, while also improving the mechanical strength and wear resistance of the coating. The two can also form a dense multilayer structure, effectively blocking the intrusion of water vapor and corrosive media, and improving corrosion resistance and durability. 3. The anti-slip floor material for sidewalks provided by the present invention has a simple preparation process, low equipment requirements, low difficulty in industrial production, and has relatively obvious economic value. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a flow chart of the construction process of the anti-slip floor material for sidewalks of the present invention; Figure 2 This is a flow chart of the preparation process of the modified covalent organic framework nanosheets of the present invention; Figure 3 This is a flow chart of the preparation process of the modified flame retardant of the present invention; Figure 4 This is a flow chart of the preparation process of the anti-slip floor material for sidewalks described in the present invention. DETAILED DESCRIPTION
[0018] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative efforts shall fall within the scope of protection of the present invention.
[0019] See also Figure 1-4 , the present invention provides a technical solution: Example 1 This embodiment provides a formula for a non-slip floor material for sidewalks, which is specifically as follows in parts by mass (one part by mass is defined as 100 g): The modified covalent organic framework nanosheets are prepared by the following steps: S11. Weigh 2.52 parts of 2,4,6-trihydroxybenzaldehyde and 1.94 parts of p-phenylenediamine by mass, add them to 20 parts of dimethyl sulfoxide, and mix them. Stir with ultrasonic assistance for 10 minutes to ensure complete mixing. S12. The mixed solution was heated in an oil bath to 120°C and reacted for 24 hours to perform a heating condensation reaction. After the reaction, the mixture was cooled to room temperature, centrifuged, washed, and dried to obtain covalent organic framework nanosheets. S13. Dispersing the covalent organic framework nanosheets in a sodium hydroxide aqueous solution with a pH of 9, reacting at 30° C. for 3 h, promoting the ring-opening and cleavage of the imine bonds at the edge of the framework to generate -NH2 and -OH hydroxyl groups, thereby increasing the hydroxyl content and obtaining the modified covalent organic framework nanosheets.
[0020] The modified flame retardant is prepared by the following steps: S21. 3 parts by mass of magnesium hydroxide nanopowder was added to 100 parts of a 1 mol / L aqueous HCl solution, ultrasonically dispersed for 10 min, and the pH of the solution was adjusted to 2; S22. 0.8 parts by mass of aniline was added to 20 parts of a 1 mol / L aqueous HCl solution and sonicated until the aniline was completely dissolved to form a homogeneous solution; S23. 1.25 parts by mass of ammonium persulfate was added to 20 parts of a 1 mol / L aqueous HCl solution and sonicated until the ammonium persulfate was completely dissolved to form a homogeneous solution; S24. The aniline solution was added to the magnesium hydroxide suspension and stirred evenly. The temperature was controlled at 3 ° C in an ice bath. The ammonium persulfate solution was added dropwise to carry out the polymerization reaction. Stirring was continued during the addition and the temperature was maintained at no more than 5 ° C. After the addition was completed, stirring was continued for 4 hours to ensure that the polyaniline was evenly coated with the magnesium hydroxide particles; S25. After the reaction is completed, the precipitate is collected by centrifugation, washed, and dried to obtain the modified flame retardant.
[0021] This embodiment also provides a method for preparing the anti-slip floor material for sidewalks, comprising the following steps: S31. The epoxy resin, polysiloxane elastic resin and fluorocarbon resin were mixed in parts by mass, and a silane coupling agent was added to enhance interfacial bonding to obtain a resin matrix; S32. The nano-silicon nitride particles, nano-silicon dioxide, nano-zinc oxide, boron nitride nanotubes, modified covalent organic framework nanosheets, attapulgite and dispersant were added to the resin matrix prepared in step S31 in order by mass, and stirred for 2h (500rpm) to mix them evenly; S33. Add the modified flame retardant, curing agent, accelerator, and leveling agent in order by mass, and continue stirring for 1 hour (500 rpm) to obtain the anti-slip floor material for the sidewalk.
[0022] In this embodiment, the brand of the epoxy resin is RDEX R 25 E; the brand of the polysiloxane elastic resin is LG-20; and the brand of the fluorocarbon resin is H06-35.
[0023] In this embodiment, the diameter of the boron nitride nanotubes is in the range of 20-50 nm; the particle size of the nano-silicon nitride is in the range of 50-100 nm; the particle size of the nano-silicon dioxide is in the range of 20-50 nm; and the particle size of the nano-zinc oxide is in the range of 10-100 nm.
[0024] In this embodiment, the curing agent is further limited to a dicyandiamide curing agent, specifically XJ-SQA1; the accelerator is further limited to a 2-methylimidazole accelerator, specifically CUREZOL 2MZ-A; the leveling agent is further limited to a polysiloxane leveling agent, specifically AC-8450; the coupling agent is further limited to a silane coupling agent, specifically KH-792; and the dispersant is BYK-2151.
[0025] This embodiment also provides a construction process for laying a non-slip floor material for a sidewalk, which includes the following steps: S1. Clean, sand and remove dust from the sidewalk base and apply primer; S2. After the primer is dry, apply the epoxy mid-coat. After the epoxy mid-coat is dry, use a roller to evenly apply the mixed sidewalk anti-slip floor material on the surface of the epoxy mid-coat. After natural curing for 15 days, the paving is completed.
[0026] Example 2: Example 2 differs from Example 1 in that, in Example 2, the formula of the anti-slip floor material for sidewalks is as follows in parts by mass (one part by mass is defined as 100 g): The remaining steps are exactly the same as in Example 2 and Example 1.
[0027] Example 3: Example 3 differs from Example 1 in that, in Example 3, the formula of the anti-slip floor material for sidewalks is as follows in parts by mass (one part by mass is defined as 100 g): The remaining steps are exactly the same as in Example 3 and Example 1.
[0028] Comparative Example Comparative Example 1: Comparative Example 1 differs from Example 1 in that the modified covalent organic framework nanosheets, boron nitride nanotubes, and nano-silicon nitride particles are omitted in Comparative Example 1, and the remaining steps are exactly the same in Comparative Example 1 and Example 1.
[0029] Comparative Example 2: Comparative Example 2 differs from Example 1 in that the modified flame retardant, attapulgite, and nano-silica are omitted in Comparative Example 2, and the remaining steps are exactly the same as those in Example 1.
[0030] Comparative Example 3: Comparative Example 3 differs from Example 1 in the following manner: in Comparative Example 3, the use of fluorocarbon resin and polysiloxane elastic resin is eliminated, and the remaining steps are exactly the same in Comparative Example 3 and Example 1.
[0031] Performance Testing According to the national standards GB / T22374-2008 and GB8624-2012, the floor materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested for performance, and the test results are shown below: As mentioned above, based on the pencil hardness and adhesion test results, Examples 1 to 3 all exhibited high hardness (8H) and excellent adhesion (Grade 0). This is attributed to the optimal ratio of epoxy resin, polysiloxane elastic resin, and fluorocarbon resin, as well as the uniform dispersion of nanofillers. The epoxy resin, as the primary hard matrix, provides the material's fundamental mechanical strength, while the polysiloxane elastic resin imparts excellent elasticity and toughness to the coating, preventing cracking due to external forces or thermal expansion and contraction. The fluorocarbon resin enhances weather resistance and surface stability. The presence of nano-modified covalent organic framework nanosheets, boron nitride nanotubes, and nano-silicon nitride particles significantly enhances the material's internal structural density and interfacial bonding, contributing to increased hardness and adhesion. In contrast, the complete omission of these nanofillers in Comparative Example 1 resulted in a sharp drop in hardness to 3H and a significant decrease in adhesion. This demonstrates that the nanofillers not only serve as reinforcements but also enhance overall mechanical properties by chemically bonding with the resin matrix to form a strong interface. Comparative Example 2 lacks the modified flame retardant, attapulgite, and nano-silica, resulting in reduced adhesion and hardness, demonstrating the importance of these components in maintaining the material's structural stability and wear resistance. Comparative Example 3, lacking the fluorocarbon resin and polysiloxane elastic resin, exhibits reduced hardness and adhesion, demonstrating that these two resins not only provide elastic cushioning but also contribute to the formation of a weather-resistant and stable coating structure. In terms of anti-slip performance, the dry anti-slip coefficients of Examples 1 to 3 ranged from 0.72 to 0.85, and the wet anti-slip coefficients also remained between 0.65 and 0.78, demonstrating excellent anti-slip effects. This is primarily due to the formation of a microscopic roughness structure on the coating surface by nanoparticles such as nano-silicon nitride, nano-silicon dioxide, and boron nitride nanotubes, which increases the surface friction coefficient. The addition of modified covalent organic framework nanosheets and attapulgite further enriches the surface morphology and enhances anti-slip performance. The comparative example group, lacking these nanofillers and functional components, had a relatively smooth surface structure, resulting in a significant decrease in anti-slip performance, particularly in the wet state, demonstrating the key contribution of nanostructures to sidewalk safety.
[0032] In the alkali resistance and acid resistance tests, the example materials all showed no obvious abnormalities, indicating that they have excellent chemical stability and can resist the erosion of strong alkali and strong acid environments. This is due to the chemical inertness of the fluorocarbon resin and the dense barrier effect of the nanofiller, which prevents the corrosive medium from penetrating into the interior of the matrix. In particular, the synergistic effect of the modified flame retardant and attapulgite not only enhances the flame retardant function, but also improves the material's resistance to chemical corrosion. In contrast, Comparative Example 1, Comparative Example 2 and Comparative Example 3 showed varying degrees of gloss loss, bulging, discoloration and peeling, and even severe corrosion, indicating that the lack of nanofillers and flame retardants makes the coating structure loose, and chemical media are easy to penetrate, resulting in performance degradation.
[0033] Wear resistance tests showed that Examples 1-3 had extremely low mass losses, ranging from 0.015% to 0.025%, respectively, demonstrating their excellent wear resistance. This is primarily due to the high hardness and uniform dispersion of nano-silicon nitride particles, nano-silicon dioxide, and boron nitride nanotubes. These nanomaterials form a robust composite network that effectively disperses external friction and prevents coating wear. The comparative group, lacking key nanofillers, experienced a significantly increased wear rate, demonstrating the irreplaceable role of nanomaterials in improving the wear resistance of the coating.
[0034] Weathering test results showed that Examples 1-3 maintained gloss retention rates of 85% to 92%, respectively, demonstrating that the materials maintained excellent appearance and performance after prolonged outdoor exposure. The UV and oxidation resistance of the fluorocarbon resin and polysiloxane elastomer resin played a key protective role. The gloss retention of the control group dropped significantly, to 55% to 70%, accompanied by noticeable aging and chalking, further confirming the lack of these two resins leading to insufficient weathering resistance.
[0035] The flame retardant performance indicators such as temperature rise in the furnace, mass loss, continuous burning time, total calorific value and critical thermal radiation flux show that Examples 1-3 all have low temperature rise, small mass loss, short burning time, low total calorific value and high critical thermal radiation flux, reflecting excellent flame retardant performance. The reason is that the composite structure of magnesium hydroxide nanopowder and polyaniline in the modified flame retardant can release water to absorb heat and cool down during combustion, while forming a carbonized protective layer to block oxygen and heat conduction, effectively inhibiting the spread of flame. Due to the lack of modified flame retardant and related functional fillers, the comparative example group has a significantly higher temperature rise, increased mass loss, longer burning time, increased total calorific value, reduced critical thermal radiation flux, and significantly reduced flame retardant performance.
[0036] This strongly proves that the anti-slip floor material for sidewalks prepared by the present invention has better hardness, anti-slip performance, acid and alkali resistance and weather resistance than the materials prepared in Comparative Examples 1-3, and has relatively excellent flame retardant properties. In addition to being used in sidewalks, it can also be used in other fire prevention places, and has broad application prospects.
[0037] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A non-slip floor material for sidewalks, characterized in that: The invention comprises the following components in parts by mass: 30-40 parts of epoxy resin, 15-20 parts of polysiloxane elastic resin, 10-15 parts of fluorocarbon resin, 4-5 parts of modified covalent organic skeleton nanosheets, 3-5 parts of boron nitride nanotubes, 10-12 parts of nano silicon nitride particles, 3-4 parts of nano silicon dioxide, 2-3 parts of nano zinc oxide, 7-8 parts of modified flame retardant, 6-7 parts of attapulgite, 4-6 parts of curing agent, 1.5-2 parts of accelerator, 0.5-1 part of leveling agent, 1-2 parts of coupling agent and 1.5-2 parts of dispersant.
2. The anti-slip floor material for sidewalks according to claim 1, characterized in that: The modified covalent organic framework nanosheets are prepared by the following steps: S11. Weigh 1-3 parts of 2,4,6-trihydroxybenzaldehyde and 1-3 parts of p-phenylenediamine by mass, add them to 20-30 parts of dimethyl sulfoxide and mix them, and stir them with ultrasonic assistance for 10-15min to ensure complete mixing; S12. The mixed solution was heated in an oil bath to 120-130°C and reacted for 24-32 hours to perform a heating condensation reaction. After the reaction, the mixture was cooled to room temperature, centrifuged, washed, and dried to obtain covalent organic framework nanosheets. S13. Dispersing the covalent organic framework nanosheets in a sodium hydroxide aqueous solution with a pH of 9-10, reacting at 30-40° C. for 2-3 hours, promoting the ring-opening and cleavage of the imine bonds at the edge of the framework to generate -NH2 and -OH hydroxyl groups, thereby increasing the hydroxyl content and obtaining the modified covalent organic framework nanosheets.
3. The anti-slip floor material for sidewalks according to claim 1, characterized in that: The modified flame retardant is prepared by the following steps: S21. 3-4 parts by mass of magnesium hydroxide nanopowder was added to 80-100 parts of a 1-3 mol / L aqueous HCl solution, ultrasonically dispersed for 10-20min, and the pH of the solution was adjusted to 2-3; S22. 0.6-1.2 parts by mass of aniline was added to 20-30 parts of a 1-3 mol / L aqueous HCl solution, and ultrasonicated until the aniline was completely dissolved to form a homogeneous solution; S23. 1.2-1.5 parts by mass of ammonium persulfate was added to 20-30 parts of a 1-3 mol / L aqueous HCl solution, and sonicated until the ammonium persulfate was completely dissolved to form a homogeneous solution; S24. The aniline solution was added to the magnesium hydroxide suspension and stirred evenly. The temperature was controlled at 0-5 ° C in an ice bath. The ammonium persulfate solution was added dropwise to carry out the polymerization reaction. Stirring was continued during the addition and the temperature was maintained at no more than 5 ° C. After the addition was completed, stirring was continued for 4-5h to ensure that the polyaniline was evenly coated with the magnesium hydroxide particles; S25. After the reaction is completed, the precipitate is collected by centrifugation, washed, and dried to obtain the modified flame retardant.
4. The anti-slip floor material for sidewalks according to claim 1, characterized in that: The anti-slip floor material for sidewalks is prepared by the following steps: S31. The epoxy resin, the polysiloxane elastic resin and the fluorocarbon resin were mixed in parts by mass, and a coupling agent was added to enhance the interfacial bonding to obtain a resin matrix; S32. The nano-silicon nitride particles, nano-silicon dioxide, nano-zinc oxide, boron nitride nanotubes, modified covalent organic framework nanosheets, attapulgite and dispersant were added to the resin matrix prepared in step S31 in parts by mass, and stirred for 2-3h to mix evenly; S33. Add modified flame retardant, curing agent, accelerator and leveling agent in order by mass, and continue stirring for 1-2 hours to obtain the anti-slip floor material for the sidewalk.
5. The anti-slip floor material for sidewalks according to claim 1, characterized in that: The diameter of the boron nitride nanotube is in the range of 20-50 nm; the particle size of the nano silicon nitride is in the range of 50-100 nm; the particle size of the nano silicon dioxide is in the range of 20-50 nm; and the particle size of the nano zinc oxide is in the range of 10-100 nm.
6. The anti-slip floor material for sidewalks according to claim 4, characterized in that: The curing agent is further limited to a dicyandiamide curing agent.
7. The anti-slip floor material for sidewalks according to claim 4, characterized in that: The leveling agent is further defined as a polysiloxane leveling agent.
8. The anti-slip floor material for sidewalks according to claim 4, characterized in that: The coupling agent is further defined as a silane coupling agent.
9. The anti-slip floor material for sidewalks according to claim 4, characterized in that: The accelerator is further defined as a 2-methylimidazole accelerator.
10. A construction process for a sidewalk anti-skid floor material, used for laying the sidewalk anti-skid floor material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Clean, sand and remove dust from the sidewalk base and apply primer; S2. After the primer is dry, apply the epoxy mid-coat. After the epoxy mid-coat is dry, use a roller to evenly apply the mixed sidewalk anti-slip floor material on the surface of the epoxy mid-coat. After natural curing for 10-15 days, the paving is completed.
Citation Information
Patent Citations
A kind of flame retardant epoxy floor coating
CN103571304B
Preparation method of polyaniline composite magnesium hydroxide flame retardant
CN109438981A
Imine bond nanoscale covalent organic framework and preparation method thereof
CN116239737A
Chiral covalent organic framework material as well as preparation method and application thereof
CN117264153A
Two-dimensional COF heterojunction material, organic-inorganic hybrid heavy anti-corrosion coating and preparation method of two-dimensional COF heterojunction material and organic-inorganic hybrid heavy anti-corrosion coating
CN118027713A
Cited By
Cold-resistant, anti-corrosion and anti-rust self-spraying particle elastic glue and preparation method thereof
CN122037722A
Cold-resistant anticorrosive and antirust self-spraying particle elastic glue and preparation method thereof
CN122037722B